Endothelium-dependent molecular mechanisms of articular cartilage and subchondral bone remodeling in conditions of cardiovascular comorbidity - M. A. Kabalyk; V. A. Nevzorova; T. S. Kovalenko; G. I. Sukhanova (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To determine the expression level of endothelial factors (VEGF-A, CD34+) in the tissues of the joints in experimental arterial hypertension (AH), hyperlipidemia (HL) and their combination.Material and methods. An experimental study was conducted on 24 sexually mature males of outbred guinea pigs. All animals were divided into 4 groups of 6 animals each. In the first group, AH was reproduced by intramuscular injection of a hydrocartisone solution. HL in the second group was simulated by intraperitoneal injection 1 time in 3 weeks of Tween 80 and diet modification. In the third group, the combination of AH and GL was reproduced by injection of a hydrocartisone solution, Tween-80 and diet modification. On the 60-day animals were pull out of the experiment by euthanasia. Hock joint tissue sampling was performed, in which the expression of endothelial vascular growth factor A (VEGF-A), CD34 was determined using a peroxidase immunohistochemical reaction.Results. It was found that during experimental AH, expression of VEGF-A increased in the subchondral bone. In experimental HL, preferential induction of VEGF-A and CD34 in the articular cartilage and subchondral bone is observed. When combined with cardiovascular factors, the highest expression of the molecular mechanisms of cardiometabolic stress, including VEGF-A and CD34 is observed.Conclusion. The results indicate that cardiovascular factors affect the joint tissue. This allows us to make an assumption that the joint tissues belong to the target organs of cardiovascular diseases and make it possible to judge the important role of cardiovascular comorbidity in the pathogenesis of degenerative inflammatory joint diseases.